Workplace Incivility in a Swedish Context - Torkelson, Eva; Holm, Kristoffer; Bäckström, Martin (Nordic Journal of Working Life Studies, 2016)
The present study investigated workplace incivility in a Swedish context. The first aim was to assess how common the phenomenon is and the second was to study which groups (gender, age, ethnicity, and power position) are most targeted by workplace incivility and are more prone to act in an uncivil way. Additionally, the relationships between experienced and witnessed incivility and wellbeing as well as instigated incivility were investigated. An online survey was administered by SIFO (the national public opinion poll agency). The collected data consist of a stratified sample whose composition is identical to the working population in Sweden (N = 3001). The results show that almost three quarters of the respondents had been the target of coworker incivility and 52% of supervisor incivility at least one to two times in the past year. Of the respondents, 75% had witnessed coworkers and 58% witnessed a supervisor treating others in an uncivil way. Furthermore, 66% had instigated uncivil acts toward others. The results also show that female and younger employees are slightly more targeted by incivility from coworkers and younger employees and supervisors are slightly more prone to instigate incivility. Moreover, it was found that that experienced incivility was the strongest predictor of low well-being and that witnessed incivility was the strongest predictor of instigated incivility.